The Raman laser spectrometer ExoMars simulator (RLS Sim): A heavy‐duty Raman tool for ground testing on ExoMars. (21st November 2021) - Lopez‐Reyes, Guillermo; Veneranda, Marco; Manrique, Jose Antonio; González Martín, Álvaro; Moral, Andoni; Perez‐Canora, Carlos; Rodríguez Prieto, Jose Antonio; Sanz Arranz, Aurelio; Saiz Cano, Jesús; Lalla, Emmanuel; Konstantinidis, Menelaos; Prieto‐Ballesteros, Olga; et al.
Abstract: The Raman laser spectrometer (RLS) instrument onboard the Rosalind Franklin rover of the ExoMars 2022 mission will analyze powdered samples on Mars to search for traces of life. To prepare for the mission, the RLS scientific team has developed the RLS ExoMars Simulator (RLS Sim), a flexible model of RLS that operates similarly to the actual instrument, both in laboratory and field conditions, while also emulating the rover operational constraints in terms of sample distribution that are relevant to the Raman analysis. This system can operate autonomously to perform RLS‐representative analysis in one or several samples, making it very useful to perform heavy experimental tasks that would otherwise be impossible using a flight‐representative model of the instrument. In this work, we introduce the current configuration of the RLS Sim that has incorporated new hardware elements such as the RAman Demonstrator 1 (RAD1) spectrometer with the objective of approaching its performance to that of the actual RLS instrument. To evaluate the scientific capability of the RLS Sim, we have compared it with a replica model of RLS, the RLS Flight Spare (FS). Several acquisition aspects have been evaluated based on the analysis of select samples, assessing the performance in terms of spectral range and resolution and also studying several issues related to the evolution of signal‐to‐noise ratio (SNR) with different acquisition parameters, especially the number of accumulations. This performance analysis has shown that the RLS Sim in its updated configuration will be a key model to perform support science for the ExoMars mission and the RLS instrument on the Rosalind Franklin rover. Designed to work intensively, the use of the RLS Sim in combination with the RLS FS will facilitate maximizing the scientific return of the RLS spectrometer during Martian operations. Abstract : In this work, we introduce the current configuration of the RLS ExoMars Simulator (RLS Sim). A laboratory model of the RLS instrument has incorporated new hardware elements with the objective of approaching its performance to that of the actual RLS instrument. This performance analysis has shown that the RLS Sim in its updated configuration will be a key model to perform support science for the ExoMars mission and the RLS instrument on the Rosalind Franklin rover. Designed to work intensively, the use of the RLS Sim in combination with the RLS FS will facilitate maximizing the scientific return of the RLS spectrometer during Martian operations.